Combining SDM-Based Circuit Switching with Packet Switching in a Router for On-Chip Networks. (4th January 2012) - Lusala Lusala, Angelo Kuti Angelo Kuti; Legat Legat, Jean-Didier Jean-Didier
Abstract : A Hybrid router architecture for Networks-on-Chip "NoC" is presented, it combines Spatial Division Multiplexing "SDM" based circuit switching and packet switching in order to efficiently and separately handle both streaming and best-effort traffic generated in real-time applications. Furthermore the SDM technique is combined with Time Division Multiplexing "TDM" technique in the circuit switching part in order to increase path diversity, thus improving throughput while sharing communication resources among multiple connections. Combining these two techniques allows mitigating the poor resource usage inherent to circuit switching. In this way Quality of Service "QoS" is easily provided for the streaming traffic through the circuit-switched sub-router while the packet-switched sub-router handles best-effort traffic. The proposed hybrid router architectures were synthesized, placed and routed on an FPGA. Results show that a practicable Network-on-Chip "NoC" can be built using the proposed router architectures. 7 × 7 mesh NoCs were simulated in SystemC. Simulation results show that the probability of establishing paths through the NoC increases with the number of sub-channels and has its highest value when combining SDM with TDM, thereby significantly reducing contention in the NoC.